2014
DOI: 10.4338/aci-2014-03-ra-0021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a federated medical search engine

Abstract: SummaryBackground: Federated medical search engines are health information systems that provide a single access point to different types of information. Their efficiency as clinical decision support tools has been demonstrated through numerous evaluations. Despite their rigor, very few of these studies report holistic evaluations of medical search engines and even fewer base their evaluations on existing evaluation frameworks. Objectives: To evaluate a federated medical search engine, MedSocket, for its potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Information retrieval [84,85] and information seeking behavior were also discussed in the context of visit note display [86] and ignoring of content [87]. The increasing use of smartphones to access personal health information routinely was described [88].…”
Section: Health Information Exchange (Hie)mentioning
confidence: 99%
“…Information retrieval [84,85] and information seeking behavior were also discussed in the context of visit note display [86] and ignoring of content [87]. The increasing use of smartphones to access personal health information routinely was described [88].…”
Section: Health Information Exchange (Hie)mentioning
confidence: 99%
“…For example, Saparova piloted a federated search system that factored in information needs of 51 clinicians. Clinicians found the search system easy and intuitive to use; however, a key piece of feedback was personalization features as the study concluded that successful adoption of a clinical information system depends on its human, technology, and organization fit [22].…”
Section: Introductionmentioning
confidence: 99%